ANALYSIS OF ACCESS TO CAPITAL IN BUSINESS ACTORS OF ORNAMENTAL PLANTS IN TOURISM VILLAGE BUNGA VILLAGE BANYUURIP KEDAMEAN ON GRESIK DISTRICT (Universitas Dr. Soetomo, 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. In their daily operations, MSMEs also face various problems, including in the financial sector. This study aims to identify the need for capital and access to capital to financial institutions. The analytical method used is the proportion. This study found that the need for micro-enterprise funds is for investment in working capital and partly in land. Business actors prioritize sources of funds from their own capital and loans in the form of merchandise from fellow business actors. There are still many business actors who are reluctant to apply for credit to cooperatives and banks because they are not members of the cooperative and the requirements to get a loan are also burdensome.